Caries Risk Assessment and Prevention - Pourhashemi SJ (Tehran University of Medical Sciences, 2000)
Over 20 years, several analytical approaches have been designed to predict caries in children."nCaries Risk Assessment is a recently developed technique concern to caries prediction."nThis procedure involves three stages as follows:"n1- Determination and assessment of the dental caries risk factors."n2- Examination and evaluation of each individual child to be specifically diagnosed the level of 3- caries risk e.g. high, moderate and low risk."n3- Recommendation of preventive programs according to risk assessment."nBecause children vary widely in their ability to develop cavities, a well-organized program holds great promise for promoting dental heath for pre-school children of varying caries risk. This article considered a series of principals that dentist can use in case planning, management and prevention programs according to risk assessment.